RADIO RECEPTOR ASSAY FOR DIAGNOSTIC SERUM AND MILK 1,25-DIHYDROXYCHOLECALCIFEROL - Hastari Wuryastuti (Jurnal Sain Veteriner, 1996)
The objectives of this study were to modify and develop technique for determination of 1,25-(OH)2D3 concentrations in sera and milk samples. The developed technique, used non-HPLC for extraction and purification of the samples and involved radio receptor assay which used calf thymus as 1,25-{OH)2Dj receptor for quantitation of 1,25-(OH)2D3 Results of this study were compare to that of the technique developed by Horst et at. (1981) which used HPLC for samples extraction and purification. The correlation between the two techniques was r=0,95. Using the modified technique the 1,25-(OH)2D3 concentrations in cow and sow sera were 57,42 ±5,3 pg/ml (n=20) and 75.22 ±6.05 pg/ml (n=20) respectively, whereas the laSHOH^D., concentrations in cow and sow milk were 16.62 ±2.2 pg/ml (n=20) and 21.52 + 3.125 pg/ml (n=20). Based on the results could be concluded that the technique that had been developed in this study was found satisfactory for determination the l,25-(OH)2Dj concentration either in serum or milk samples.